2019
DOI: 10.1002/mabi.201900184
|View full text |Cite
|
Sign up to set email alerts
|

dPGS Regulates the Phenotype of Macrophages via Metabolic Switching

Abstract: The synthetic compound dendritic polyglycerol sulfate (dPGS) is a pleiotropic acting molecule but shows a high binding affinity to immunological active molecules as L‐/P‐selectin or complement proteins leading to well described anti‐inflammatory properties in various mouse models. In order to make a comprehensive evaluation of the direct effect on the innate immune system, macrophage polarization is analyzed in the presence of dPGS on a phenotypic but also metabolic level. dPGS administered macrophages show a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…The growing body of literature shows that the immunological functions of macrophages are related to a metabolic switch from oxidative phosphorylation to glycolysis. In agreement with this notion, we found that TSG markedly modulated the intracellular metabolism of macrophages and reversed their metabolic profiling from M1 toward the M2 subset (Figure A). The underlying mechanism by which TSG significantly promoted the M2 switch of macrophages may be related with its alteration of intracellular energy metabolic pathway used.…”
Section: Discussionsupporting
confidence: 84%
“…The growing body of literature shows that the immunological functions of macrophages are related to a metabolic switch from oxidative phosphorylation to glycolysis. In agreement with this notion, we found that TSG markedly modulated the intracellular metabolism of macrophages and reversed their metabolic profiling from M1 toward the M2 subset (Figure A). The underlying mechanism by which TSG significantly promoted the M2 switch of macrophages may be related with its alteration of intracellular energy metabolic pathway used.…”
Section: Discussionsupporting
confidence: 84%